Analisis Manajemen Risiko Petani dalam Rangka Konversi Lahan Perkebunan Karet Menjadi Lahan Perkebunan Kelapa Sawit di Banyuasin III, Kabupaten Banyuasin - Aritonang, Christian Yosua Salomo (Journal of Management and Creative Business, 2026)
The conversion of rubber plantations to oil palm plantations in Banyuasin III has shown a significant increase in recent years, driven by low rubber prices and relatively stable palm oil prices. This occurs despite persistent demand for rubber, which is actually experiencing limited supply due to land conversion and a reduction in the number of processing plants. This study aims to analyze farmers' risk management in the land conversion process, with a focus on production and financial risks. The method used was a quantitative approach through a survey of 50 farmers selected purposively. Data analysis was conducted using descriptive statistics and the coefficient of variation to measure risk levels, and regression analysis to examine the effect of risk on farmer income. The results indicate that financial risk is a major challenge, primarily related to the high initial investment costs and loss of income during the immature period. Meanwhile, production risk is relatively more manageable. Farmers implement various adaptive strategies such as business diversification, the use of superior seeds, and involvement in farmer groups. This study emphasizes the importance of financial support and strengthening farmer capacity in managing risk to support the sustainability of agribusiness.